MANAGING STEROIDS IN A FEMALE WITH NCCAH COMPLICATED WITH COVID-19 IN PREGNANCY - Nandini, Norisha (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION We report a case of a female with Non-Classical Congenital Adrenal Hyperplasia (NCCAH) which was complicated by COVID-19 during her pregnancy. This is the second such case to be reported so far; the first being in Italy in 2020. The role of steroid management throughout her pregnancy is highlighted. CASE This is a case of a 28-year-old female diagnosed with NCCAH since age 21 and maintained on oral prednisolone 7.5 mg OD pre-pregnancy. At the 20th week of gestation, she was switched to oral hydrocortisone 10 mg BD as she developed mild Cushingoid features. Consequently, she presented at 30 weeks of gestation to the ED with symptoms of breathlessness, dehydration and compensated shock and was diagnosed with COVID-19 Category 5. She received fluid boluses and low-dose inotrope and was placed under ICU care due to worsening hypoxia. She was initiated on maintenance fluids and Remdesivir for COVID-19 and intravenous hydrocortisone 100 mg bolus with maintenance of 50 mg QID to prevent an adrenal crisis. In the ICU, her condition stabilized with inotropic and oxygen support weaned off. Her intravenous hydrocortisone was maintained at 50 mg QID. Throughout her stay, no foetal compromise was observed. She was discharged well on day 5 of illness with a supraphysiological dose of hydrocortisone 20 mg/10 mg. Further steroid adjustments were planned at the outpatient clinic on follow-up. CONCLUSION Managing acute COVID-19 infection during late pregnancy, especially with an underlying adrenal condition, poses significant challenges due to therapeutic uncertainties. A multidisciplinary team and close ICU monitoring were vital for ensuring a successful outcome for both mother and child. Steroid management in NCCAH patients, particularly during pregnancy, is critical. Early treatment with appropriate antivirals and steroids can mitigate illness progression and severity, reducing morbidity and mortality associated with COVID-19.